Desenvolvimento rural e agricultura familiar em áreas de Intervenção estatal: o caso do assentamento eldorado dos Carajás II (RN) - Medeiros, Kerginaldo Nogueira de (2015)
The relationship between family farming and rural development is a quite obvious theme in the scientific and political debates. The complexity of this relationship is compounded, among other things, because of the need of a review in the agricultural policies which could be able to reduce social inequalities. The expropriation of lands belonged to the company so called Mossoró Agro-Industrial SA (MAISA), held in 2003, giving some people the change to raise a settlement called Eldorado dos Carajás II, located between the cities of Mossoró and Baraúna, both in the state of Rio Grande do Norte, raising high expectations for the success of the agricultural policy project due to that pioneer company owned irrigated horticulture in the semiarid and also its regional and structural dimensions. After more than 10 long years as well as after the building of the Settlement Project is appropriate to examine ways of organizing production and its labor, its administrative level and its technical standard of the family farming, considering the government influence of intervention and the lack of specific official data evaluating the agricultural policy projects. The assumption is that the process of production, administrative and technological structure did not occur as planned and the government intervention occurs in a timely and insufficient way not to effectively promote the dynamics of sustainable rural development. The goal of this research is to analyze the family farming in this called Eldorado dos Carajás II Settlement Project (RN) for sustainable rural development, considering the productive structuring processes, administrative, technological and social organization. The methodology was based on a real study with a questioning in 2014, and it obtained data about the last crop year 2013, for a sample of 89 families distributed among 10 rural villages of the Settlement Project and the heads of associations. Secondary data issued by public agencies to strengthen analysis of the family farming dynamics were also used. The results lead to an unproductive or low agricultural productivity of the majority of the settlers by using low cost technology and featuring a concentration of existing production in a few families. For more than 50% of the families the pluriactivity is a strategy to better their income and a significant amount of them have enrolled in some kind of government social programs or policies, especially the social security department and the family allowance programs. The main destination of the existing production is marketing it through middlemen, with an inexpressible access to institutional markets (Food Acquisition Program - PAA and National School Feeding Program - PNAE). In relation to the sustainable agricultural practices only 25,84% of the families had agroecological cultures. The social and administrative organization is limited to the representation of activities before public bureaus and management of the infrastructure of the rural villages, but it also supplies the government absence help in some collective services. Despite this present life context most of the families believe in the agricultural future and are satisfied with the present agricultural activities and rural areas. The main conclusion is that the government help is significant and timely through welfare programs, but it does not promote the expected dynamics of the sustainable rural development